Implementasi Good Governance di Kecamatan Pasan Kabupaten Minahasa Tenggara - Rondonuwu, Andre; Rompas, Welson Yappi; Pombengi, Jericho Denga (JURNAL ADMINISTRASI PUBLIK, 2015)
ABSTRAK : Sub-district is the district / city that has an important position and role in the framework of theeffectiveness of the regional administration, so it must be able to effectively implement good governance.Accordingly, the study is intended to answer the question "how the implementation of good governance in thesub-district government Pasan Southeast Minahasa regency.From the literature review determined the six principles of good governance are the focus of research, namely:participation, transparency, responsiveness, fairness, of efficiency and effectiveness, and accountability.This study was designed as a descriptive survey research. Sources of data / research informants are allgovernment civil servants districts Pasan many as 22 people, and the citizens of 30 people were taken in fivevillages in the sample, so that the total number of respondents / informants there were 52 people. Primary datacollection using questionnaire techniques and assisted with the interviews. Data analysis was performed usingdescriptive statistical analysis and the percentage frequency distribution analysis.The result showed that the implementation of the principles of good governance (participation,transparency, responsiveness, fairness, efficiency and effectiveness, akuintabilitas) in the sub-district governmentPasan is still at the level of the medium category, but it is good enough.Based on the results of these studies conclude that implementation of good governance can not berealized optimally by Pasan sub-district government, however, has been quite good.Departing from these studies it is necessary to attempt to improve the implementation of goodgovernance in the sub-district government Pasan by doing several things, among others, namely: to increase thenumber of employees, improving employee competence of human resources, adds to the means and facilities tosupport the implementation of tasks, and increase the commitment of forces to realize good governance inoptimal.Key Word : Good Governance